2021
DOI: 10.3389/fncir.2021.659557
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor Adaptation Brain Changes During a Spaceflight Analog With Elevated Carbon Dioxide (CO2): A Pilot Study

Abstract: Astronauts on board the International Space Station (ISS) must adapt to several environmental challenges including microgravity, elevated carbon dioxide (CO2), and isolation while performing highly controlled movements with complex equipment. Head down tilt bed rest (HDBR) is an analog used to study spaceflight factors including body unloading and headward fluid shifts. We recently reported how HDBR with elevated CO2 (HDBR+CO2) affects visuomotor adaptation. Here we expand upon this work and examine the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Importantly, these findings provide the possibility that CO 2 homeostasis in the brain may be altered via modified CO 2 regulatory mechanisms in space. Indeed, it has been reported that long-term microgravity decreased cognitive function (Salazar et al, 2020(Salazar et al, , 2021 and that this is associated with impaired CVR (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these findings provide the possibility that CO 2 homeostasis in the brain may be altered via modified CO 2 regulatory mechanisms in space. Indeed, it has been reported that long-term microgravity decreased cognitive function (Salazar et al, 2020(Salazar et al, , 2021 and that this is associated with impaired CVR (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We processed the dual task data from the HDBR and HDBR + CO 2 subjects using identical procedures to our past work ( Hupfeld et al, 2020a ; Salazar et al, 2020 , 2021 ) using the established Statistical Parametric Mapping software (SPM12, version 7219) ( Ashburner et al, 2016 ) and pipeline ( Penny et al, 2011 ; Ashburner et al, 2016 ) through MATLAB R2016a (version 9.0). We first corrected functional images for slice timing and realigned the images to correct for volume-to-volume head motion.…”
Section: Methodsmentioning
confidence: 99%
“…Montreal Neurological Institute template-based normalization does not accurately warp the cerebellum ( Diedrichsen, 2006 ; Diedrichsen et al, 2009 ). Instead, identical to our past work ( Hupfeld et al, 2020a ; Salazar et al, 2020 , 2021 ), we implemented a combination of two optimized cerebellar processing pipelines, CEREbellum Segmentation (CERES) ( Romero et al, 2017 ) and the Spatially Unbiased Infratentorial Template (SUIT) ( Diedrichsen, 2006 ; Diedrichsen et al, 2009 ). We used CERES to extract and segment the cerebellum, according to a cerebellum-specific tissue type probability map and the T1-weighted image from each subject and session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our past work (Hupfeld et al, 2021b;Salazar et al, 2020Salazar et al, , 2021, we applied specialized preprocessing steps to the cerebellum to produce cerebellar volume maps, with improved normalization of the cerebellum (Diedrichsen, 2006;Diedrichsen et al, 2009). We entered each participant's whole-brain T 1 -weighted image into the CEREbellum Segmentation (CERES) pipeline (Romero et al, 2017).…”
Section: Cerebellar Volumementioning
confidence: 99%